Health professional's perspectives of the barriers and enablers to cancer care for Indigenous Australians. (March 2016) - Meiklejohn, J.A.; Adams, J.; Valery, P.C.; Walpole, E.T.; Martin, J.H.; Williams, H.M.; Garvey, G.
Abstract : To investigate health professionals' perspectives about factors that impede or facilitate cancer care for Indigenous people. Semi‐structured interviews with 22 health professionals involved in Indigenous cancer care. Data were interpreted using an inductive thematic analysis approach. Participants presented their perspectives on a number of barriers and enablers to Indigenous cancer care. Barriers were related to challenges with communication, the health system and coordination of care, issues around individual and community priorities and views of cancer treatment and health professional judgement. Enablers to cancer care were related to the importance of trust and rapport as well as health care system and support factors. The findings highlighted the need for recording of Indigenous status in medical records and a coordinated approach to the provision of evidence‐based and culturally appropriate cancer care. This could go some way to improving Indigenous patient's engagement with tertiary cancer care services.